Psychological preparation for the Olympic Games - Gould, D.; Maynard, I. (Journal of Sports Sciences, 2009)
We review research literature on psychological preparation for Olympic Games performance. We address research identifying psychological characteristics associated with Olympic performance success, studies examining how these attributes are developed, stress and coping in Olympians, evaluation studies of the Olympic experience with particular emphasis on factors influencing performance, and the best practice literature on effective Olympic psychological consultations. Key principles are identified as well as gaps in the knowledge base that need to be addressed by investigators. Finally, implications for preparing individual athletes, coaches, and teams are discussed.